Estimating abundances, densities, and interspecific associations in a carnivore community. Issue 5 (20th June 2019) - Forsyth, David M.; Ramsey, David S. L.; Woodford, Luke P.
ABSTRACT: Estimating population abundances, densities, and interspecific interactions are common goals in wildlife management. Camera traps have been used to estimate the abundance and density of a single species, and are useful for carnivores that occur at low densities. Spatial capture–recapture (SCR) models can be used to estimate abundance and density from a camera trap array when all, some, or no individuals in the population can be uniquely identified. These SCR models also estimate locations of individual activity centers, the spatial patterning of which could provide important information about interspecific interactions. We used SCR models to estimate abundances, densities, and activity centers of each of 3 carnivore species (i.e., dingo [ Canis familiaris ], red fox [ Vulpes vulpes ], and feral cat) using photographs from 1 camera trap array in southeastern Australia during September to November 2015. Some dingoes and feral cats were uniquely identifiable and therefore, we used a spatial mark–resight model for these species. We could not uniquely identify fox individuals, however, so we used a spatial unmarked (SUN) model for this species. Our estimated dingo density was 0.06/km 2 . The fox (0.25/km 2 ) and feral cat (0.16/km 2 ) densities are within the ranges previously reported for these species in Australia. We obtained a relatively imprecise fox density estimate because we did not have detections of uniquely identifiable individuals; hence, the SUN model should be used as a last resort. We next modeled spatial dependence among the estimated activity centers for the 3 species using a spatial pair correlation function for a marked point process. Consistent with our expectations, the activity centers of dingoes and foxes were strongly negatively associated at distances of <1, 000 m. Foxes and feral cats were also negatively associated at distances of <1, 500 m. Surprisingly, dingoes and feral cats were positively associated at distances of >500 m, with no association evident at distances of <500 m. Our study extends the inferences that can be made from using a camera trap array and SCR methods to include spatial patterning and interspecific interactions, and provides new insights into the carnivore community of dingoes, foxes, and feral cats in southeastern Australia. © 2019 The Authors. The Journal of Wildlife Management Published by Wiley Periodicals, Inc. Abstract : We used spatial capture–recapture models to estimate abundances, densities, and interspecific spatial associations of 3 carnivore species (dingo, red fox, and feral cat) using photographs from one camera‐trap array in southeastern Australia. Our methods can be used to estimate abundances, densities, and interspecific spatial associations elsewhere, providing robust information that will greatly assist managers and researchers working with wildlife communities.